Modeling the evolution of loess-covered landforms in the Loess Plateau of China using a DEM of underground bedrock surface - Xiong, Li-Yang; Tang, Guo-An; Li, Fa-Yuan; Yuan, Bao-Yin; Lu, Zhong-Chen (Geomorphology (Amsterdam, Netherlands), 2014)
The evolution of loess-covered landforms is largely controlled by the pre-Quaternary underlying bedrock terrain, which is one of the most important factors in understanding the formation mechanism of the landforms. This study used multiple data sources to detect 1729 outcropping points of underlying terrain, in order to construct a digital elevation model (DEM) of the paleotopography of an area of the Loess Plateau subject to severe soil erosion. Four terrain characteristics, including terrain texture, slope gradient, the hypsometric curve, and slope aspect, were used to quantify topographic differences and reveal the loess-deposition process during the Quaternary. A loess thickness map was then created to show the spatial distribution of loess deposits in the test area. Finally, the geomorphological inheritance characteristics of the loess-covered landforms were evaluated in different landform divisions. The results showed the significant inheritance of modern topography from the underlying topography with a similar general relief trends. The average thickness of loess deposits was computed to be 104.6m, with the thickest part located in the Xifeng loess tableland area. In addition, the slope aspects of the North and Northwest seem to have favored Quaternary loess deposition, which supported the hypothesis of an eolian origin for loess in China. The modern surface has lower topographic relief compared to the underlying terrain due to loess deposition. •We construct a simulated DEM of pre-Quaternary underlying paleotopography.•Significant landform inheritance from underlying terrain to modern terrain.•Slope aspect result supports the hypothesis of an eolian origin for loess.•The average thickness of loess is 104.6m.